Lindblad master equation : applications to tunnelling current - Yuen Wei Rong, Joel (2019)
In this thesis, we study an electron transport phenomenon observed in silicon coupled quantum dots called Lifetime-Enhanced Transport. We propose an energy-dependent tunnelling model to describe this phenomenon that extends previous works by adding the eﬀects of a ﬁnite magnetic ﬁeld and spin-orbit interaction. We explore the parameter space of our model through simulations and show that in certain parameter regimes, Lifetime-Enhanced Transport can no longer be observed. The simulations demonstrates that suﬃciently (1) weak singlet (coherent) tunnel coupling strength, (2) transparent tunnel barrier and (3) strong spin-orbit interaction leads to the disappearance of Lifetime-Enhanced Transport.